2014
DOI: 10.1111/1475-4932.12115
|View full text |Cite
|
Sign up to set email alerts
|

Agglomeration Economies and Productivity Growth in Manufacturing Industry: Empirical Evidence from Indonesia

Abstract: This study examines the effect of agglomeration economies on productivity growth in Indonesian manufacturing industries during the first decade of this century. Productivity growth is measured at the firm level using the Färe‐Primont Productivity Index. Each firm's productivity growth is then regressed against a set of firm and industry characteristics, including three measures of agglomeration representing the effects of specialisation, diversity and competition. The results show evidence of a positive specia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 57 publications
2
19
0
7
Order By: Relevance
“…In the case of Indonesia, the present paper partly supports the findings in Sjöholm (1999)-finding strong evidence of diversity on productivity growth-and the findings in Widodo et al (2014)-identifying specialization as having positive effects on city growth and diversity having negative effects. However, our method is different from the previous literature.…”
Section: Analysis Of the Tfp Growth Modelssupporting
confidence: 89%
“…In the case of Indonesia, the present paper partly supports the findings in Sjöholm (1999)-finding strong evidence of diversity on productivity growth-and the findings in Widodo et al (2014)-identifying specialization as having positive effects on city growth and diversity having negative effects. However, our method is different from the previous literature.…”
Section: Analysis Of the Tfp Growth Modelssupporting
confidence: 89%
“…Kuncoro (2009) mentioned that the impact of agglomeration in term of localization and urbanization economies enhance labor productivity in Jakarta and Surabaya metropolitan areas in three periods of 1990-1995, 1997-2000, and 2001-2003, emphasizing that localization economies are more significant than urbanization economies. Similarly, agglomeration will improve the productivity growth (Rizov et al, 2012;Widodo et al, 2015;Hu et al, 2015). Azari et al, (2016) also found that the urban labor productivity is determined by traditional inputs of agglomeration economies.…”
Section: Plsmentioning
confidence: 96%
“…The elasticity for capital per labor is relatively small (0.175). This condition is explained by the structure of the manufacturing industry in Indonesia, which is commonly dominated, by light or laborintensive industries (Hill, 1990a;Hill, 1990b;Widodo et al, 2015). The capital-intensive industries are typically related to heavy-processing industries such as chemical products or heavy-engineering industries such as machinery and transport equipment.…”
Section: Plsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results provide new insights into the rapid growth since 1981, particularly the north and center west of Brazil. Widodo et al (2014) examined the effect of agglomeration economies on productivity growth in Indonesian manufacturing industries. They found evidence of a positive specialization effect and a negative diversity effect for aggregate manufacturing and sub-sectors.…”
Section: Agglomeration Economies Externalities and Regional Growth: mentioning
confidence: 99%